Interdisciplinary collaboration in geriatrics: implications for social work profession in Nigeria - Emmanuel Temitope, Adaranijo (Magyar Gerontológia, 2023)
With age comes the rising demand for health care and even more peculiarities to care giving. In addition to biological changes are socioeconomic factors that impact the health and treatment of the elderly population. The dynamics involved in providing adequate care for the elderly population as seen in developed societies reveals that there is no watertight compartment to knowledge and the need for interdisciplinary collaborations.